PREVALENCE OF NEOSPORA CANINUM IN SHEPHERD DOGS OF A LIVESTOCK FARM IN THE SOUTHERN HIGHLANDS OF PERU - Vega O., Luis (2010)
Neosporosis is a parasitic disease that affects several domestic and wild mammals. Among them, it is important in the bovine species because affect reproduction causing abortions, and in canine species as it is the definitive host and a dissemination source for the disease. The aim of the present study was to determine the prevalence of Neospora caninum in shepherd dogs from five production areas of the Rural Alianza enterprise located in the southern highlands, Puno. It was collected 122 samples of canine sera during February and March 2004, and they were analyzed using the Indirect Immunofluorescence assay (IFA), in a dilution of 1:50. A total prevalence of 14.8 ± 6.3% (18/122) was found. Statistical association between rearing area (five areas of the farm), sex, and age (<1, 1-7, > 7 years of age) through the chi square test was not found. This study showed that dogs from Rural Alianza showed a moderated prevalence for Neospora caninum. Besides, the prevalence reported is related to prevalence found for South American camelids and grazing cattle in Puno, which would indicate a close relationship between definitive and intermediate host, facilitating the horizontal transmission.